Gerakan Dakwah Ahmadiyah: Pengorganisasian Komunitas dalam Misi Spiritualitas dan Sosial - Haryono Hadi Kuswanto; Suparto Suparto (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2024)
The Ahmadiyya missionary movement is an interesting socio-religious phenomenon to study, especially in the context of its community organization in spiritual and social missions. Since its establishment in 1889 by Mirza Ghulam Ahmad in Qadian, India, Ahmadiyah has experienced various reactions, both positive and negative, among the community, particularly among Muslims. This research aims to explore the organizational structure of Ahmadiyah, which includes various communities such as Ansharullah, Lajnah Imaillah, and Khuddam, as well as the missionary strategies they implement. The research method used is descriptive qualitative with a library study approach. The research results show that Ahmadiyah not only focuses on the dissemination of Islamic teachings but also commits to social activities aimed at improving the quality of life in the community. The missionary activities carried out through these communities reflect the integration of spiritual values and social actions aimed at building a better understanding of Islam in society.